Elections in Japan, Korea, and Taiwan under the single non-transferable vote : the comparative study of an embedded institution - Grofman, Bernard (Ann Arbor : The University of Michigan Press, 1999)
"In this volume, a distinguished group of scholars look at the impact of one electoral rule - the single non-transferable vote (SNTV) - on electoral competition in Japan, Korea, and Taiwan. Under the single non-transferable vote, each voter is allowed one vote although there is more than one seat to be filled."
"Through comparative studies of the adoption and rejection of SNTV and the consequences of its use in various settings, the contributors explore the differences in the operation and the effects of the application of one rule in three different countries. Arguing that any single feature of a political system is embedded in a political structure and cannot be understood without studying its relationship with other parts of the political system, the authors demonstrate how the same rule can have different consequences depending on the context in which it operates."--Jacket.
The politics of reform in Japan's lower house electoral system / Brian Woodall -- Politics of electoral reforms and practices: the case of Korean SNTV elections under the Yushin Constitution / Sung-Chull Lee -- Manipulating the electoral system under the SNTV: the case of the Republic of China on Taiwan / John Fuh-sheng Hsieh -- Organizing one's support base under the SNTV: the case of Japanese Koenkai / Jean-Marie Bouissou -- Campaigning for the Japanese diet / Haruhiro Fukui and Shigeko N. Fukai -- Candidate evaluation and voting choice under the Japanese electoral system / Ichiro Miyake -- Campaigning in an SNTV system: the case of the Kuomintang in Taiwan / I-Chou Liu -- The fragmentation effect of SNTV in Japan / Steven R. Reed and John M. Bolland -- The SNTV and the politics of electoral systems in Korea / Jongryn Mo and David Brady -- The votes mattered: decreasing party support under the Two-Member-District SNTV in Korea (1973-1978) / Kap-Yun Lee -- Electoral equilibria on Taiwan / Edwin A. Winckler -- SNTV and STV compared: their political consequences in Japan, Ireland, and Malta / Arend Lijphart -- Measuring the ties that bind: electoral cohesiveness in four democracies / Kathleen Bawn, Gary W. Cox, and Frances Rosenbluth -- SNTV, STV, and Single-Member-District systems: theoretical comparisons and contrasts / Bernard Grofman -- The electoral economy of SNTV in Japan and Taiwan / Edwin A. Winckler -- Seat bonuses under the single non-transferable vote system: evidence from Japan and Taiwan / Gary W. Cox and Emerson Niou -- SNTV: An inventory of theoretically derived propositions and a brief review of the evidence from Japan, Korea, Taiwan, and Alabama / Bernard Grofman.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Elections -- Japan; Elections -- Korea (South); Elections -- Taiwan; Élections -- Japon; Élections -- Corée du Sud; Élections -- Taiwan; POLITICAL SCIENCE -- Political Process -- General; POLITICAL SCIENCE -- Political Process -- Elections; SOCIAL SCIENCE -- Ethnic Studies -- General; Elections; Japan; Korea (South); Taiwan; Aufsatzsammlung; Südkorea; Taiwan; Wahl; Japan; Kiesstelsels; Verkiezingen; Élections -- Japon; Élections -- Corée (République); Élections -- Taiwan; 89.57 political participation; Electronic books